Fermentation bed farming improves behavioral expression and stress resistance in geese - Li, Haoyan; Yang, Jieyu; Zhang, Jiexing; Zhao, Lingbin; Zhou, Tong; Chen, Hongsheng; Li, Jiawei; Zhao, Shuai; Yin, Guoan (Frontiers in Veterinary Science, 2026)
IntroductionConventional livestock farming restricts the expression of natural behaviors and exacerbates animal stress responses. This study investigated the effects of fermentation bed farming, a novel welfare-oriented system, on the behavior and stress resistance of geese.Methods240 Northern White Geese (‌Anser cygnoides) were randomly assigned to either a flat-floor farming (Ct group) or a fermentation bed farming (Tre group). Data of behavioral patterns and post-transport blood parameters were analyzed.ResultsCompared to the Ct group, the Tre group showed significantly longer durations of sitting, walking, cage pecking, and comforting behaviors, while reduced standing and feather pecking behaviors (p < 0.05). Post-transport, serum levels of HSP70, HSP90, CORT, SP, Hpt, IL-2, IL-6, and MDA were significantly lower in the Tre group (p < 0.05), whereas levels of IgA, IgG, IgM, IL-4, SOD, and GSH-Px were significantly higher (p < 0.05).DiscussionIn conclusion, fermentation bed farming improves behavioral expression and enhances stress resistance in geese.